The Children Learning in Science (CLIS) Model on Critical Thinking Skills - Yusup, Hendrik Widya; Widodo, Ari (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
This research is motivated by a lack of primary school students’ critical thinking skills. This research was conducted to recognize the influence of the CLIS learning model on the student's critical thinking skills on natural science subjects on the material of phase transition in fourth grade. This research employed a quantitative approach with a quasi-experiment, namely the nonequivalent group pretest-posttest control group design. The sources of data in this research were 40 fourth-grade students in one of the primary schools in Sumedang Regency, which was divided into 20 students in the experimental class and 20 students in the control class. The research results revealed that the CLIS learning model influenced the students’ critical thinking ability.